Veni vidi vici?: using the tree tagger on Latin texts - Nunn, Christopher Alexander (Interdisciplinary forum of digital textual sciences, 2018)
“I think, yes, it’s also available with Latin texts,” Ines Rehbein and Josef Ruppenhofer answered during a lecture in one of our InFoDiTex sessions on my request. Immediately, I was e…